Dynamic Friction Models and Control Design - de Wit, C. Canudas; Olsson, H.; Astrom, K.J.; Lischinsky, P. (American Control Conference, 1993, 1993)
In this paper we propose two new dynamic friction models that include most of the relevant properties that friction has been observed to have (Stribeck effect, hysteresis behavior, spring-like characteristics in stiction and stick-slip regime). Properties of these models that are relevant to control design are studied. In particular we analyse the dissipative properties of the models. New control strategies are investigated and stability results are presented.